Mutating for Good: DNA Damage Responses During Somatic Hypermutation - Pilzecker, Bas; Jacobs, Heinz (Frontiers in immunology, 2019)
Somatic hypermutation (SHM) of immunoglobulin ( ) genes plays a key role in antibody mediated immunity. SHM in B cells provides the molecular basis for affinity maturation of antibodies. In this way SHM is key in optimizing antibody dependent immune responses. SHM is initiated by targeting the Activation-Induced Cytidine Deaminase (AID) to rearranged V(D)J and switch regions of genes. The mutation rate of this programmed mutagenesis is ~10 base pairs per generation, a million-fold higher than the non-AID targeted genome of B cells. AID is a processive enzyme that binds single-stranded DNA and deaminates cytosines in DNA. Cytosine deamination generates highly mutagenic deoxy-uracil (U) in the DNA of both strands of the loci. Mutagenic processing of the U by the DNA damage response generates the entire spectrum of base substitutions characterizing SHM at and around the initial U lesion. Starting from the U as a primary lesion, currently five mutagenic DNA damage response pathways have been identified in generating a well-defined SHM spectrum of C/G transitions, C/G transversions, and A/T mutations around this initial lesion. These pathways include (1) replication opposite template U generates transitions at C/G, (2) UNG2-dependent translesion synthesis (TLS) generates transversions at C/G, (3) a hybrid pathway comprising non-canonical mismatch repair (ncMMR) and UNG2-dependent TLS generates transversions at C/G, (4) ncMMR generates mutations at A/T, and (5) UNG2- and PCNA Ubiquitination (PCNA-Ub)-dependent mutations at A/T. Furthermore, specific strand-biases of SHM spectra arise as a consequence of a biased AID targeting, ncMMR, and anti-mutagenic repriming. Here, we review mammalian SHM with special focus on the mutagenic DNA damage response pathways involved in processing AID induced Us, the origin of characteristic strand biases, and relevance of the cell cycle.